Determination of SCC Contributed by DFIG Under Asymmetrical Short Circuit Fault - Wenjia Xu; Yalou Li; Peipeng Zhou; Bin Han; Zutao Xiang (CSEE Journal of Power and Energy Systems)
For the past decades, practical calculation method of short circuit current (SCC) contributed by doubly fed induction generator (DFIG) under asymmetrical short circuit fault is deficient due to its control strategies and unlinear equipment. Asymmetrical SCC of DFIG is much more complicated and may be higher than that of a symmetrical fault in some situations. To address the problem, analytical derivations of SCC under asymmetrical faults are presented by establishing current equations between DFIG windings and converter controller or crowbar protection. Each frequency component could be directly extracted from time-domain expressions. Furthermore, clear mathematical models of asymmetrical peak and steady-state SCC used for practical calculation of power systems are proposed. Simulation results verify the effectiveness and robustness to different parameters and fault conditions of the proposed method. Finally, the influences of possible parameters on characteristics of asymmetrical SCC are summarized based on the proposed method.